Commercial compact fusion triggered REBCO tape industry: Pulsed laser deposition technology opportunities and challenges - Zhao, Yue; Wu, Yue; Goyal, Amit; Huhtinen, Hannu; Paturi, Petriina; Tsuchiya, Yuji (Elsevier BV, 2026)
The rapid rise of commercial compact fusion devices has triggered fast-growing demand for high-temperature superconducting tapes, creating a major opportunity for the high-temperature superconducting (HTS) tape industry. Pulsed laser deposition (PLD) has been extensively applied for fabrication of heteroepitaxial HTS wires or tapes based on REBCO-type superconductor, also referred to as, coated conductors (CCs). A combination of multi-plume, multi-turn deposition technique and use of high-power excimer lasers has enabled and accelerated the industrialization of REBCO coated conductors. Currently, the annual production of top-tier PLD-based, HTS-wire manufacturers exceeds 3,000 km-12 mm, contributing to over half of the total global HTS wire production. PLD-REBCO tapes have demonstrated excellent in-field performance (Ic > 200 A-4 mm @20K, 20T, B//c) and competitive pricing (∼$20/m). PLD technology continues to evolve, demonstrating strong competitive advantages. However, challenges remain in further cost reduction, process stability, and increasing efficiency of raw material utilization. AI-based data mining and tackling emerging fundamental issues are seen as potential solutions to further improve stability and performance.